Vitamin D study: a retrospective comparison between two tropical countries: India and Bahrain - Kushawaha, Rajkumar; Sinkar, Prachi; Iyer, Sandhya; Velumani, Amruta; K, Kallathikumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypovitaminosis D is a very common prevalence in India as well as Middle East. Studies indicate the frequency to be anywhere between 44-96% among adults in Middle east, while in India it is estimated to range in between 50 – 94%. Our report is an attempt to study vitamin D status from two tropical countries; India and Bahrain and present status of vitamin D deficiency as well as insufficiency in a comparison summary. Methods: This retrospective study in our reference lab included data from a total of 2591 samples from Bahrain and 2596 samples from India. Serum vitamin D estimation was done by chemiluminescence immunoassay or CLIA and reported as per the classification given by the US Endocrine Society. Our reference laboratory provides diagnostic services to Bahrain and thus data from both the countries were available for analysis. Results: Our analysis detected vitamin D deficiency to be 66.2% among samples from India in comparison to 41.4% from Bahrain, and this difference was statistically significant at p<0.0001. Further, the average vitamin D levels in the cohort were detected to be higher in Bahrain samples at 24.0±11.6 ng/ml in comparison to samples from India at 18.2±14.4 ng/ml and statistically significant at p<0.0001. Conclusions: Many studies have documented the prevalence of hypovitaminosis D in a region-specific manner. Our report presents the picture of vitamin D status between two tropical countries to highlight the difference in vitamin D deficiency prevalence in two arid and semi-arid regions of the world.